How Does Credit Default Swap Premiums Affect the Turkish Financial Markets - Oner, Hakan; Oner, Selma (Quarterly Journal of Econometrics Research, 2022)
One of the most important risks of today’s financial markets is credit risk. Credit risk is very important for investors investing in international markets, and therefore it is vital to manage credit risk correctly. Credit Default Swaps (CDS) are at the forefront of the most important financial products that ensure the elimination of credit risk. In this study, the relationship between 5-Year Turkey CDS premium, which is an important indicator for investors, Turkish Borsa Istanbul (BIST) 100 Index, USDTRY foreign exchange rates and 2-Year Turkish benchmark bonds interest rates are examined. For this purpose, econometric analysis was applied using CDS premium, BIST 100 index, USDTRY and 2-Year Turkish benchmark bonds interest rate data, which consists of 2921 daily observations from 10 March 2010 to 08 March 2022. Augmented Dickey-Fuller and Phillips-Perron root tests are used to determine the stationarity of the variables. Then, the Granger Causality test, Impulse-Response Function and Variance Decomposition Analysis are used. According to the results of the study; a bilateral causality relationship was determined between CDS premiums and BIST 100 index, USDTRY exchange rate and benchmark bond interest rates. According to the Impulse-Response functions analysis, a 1% increase in CDS premium prices increases the USDTRY rate and benchmark bond interest rates, while lowering the BIST 100 index.